Figures of repetition in the old Provençal lyric : a study in the style of the troubadours - Smith, Nathaniel B. (North Carolina studies in the Romance languages and literatures, 1976)
Nathaniel Smith provides an analysis that draws attention to the esthetics of Provencal troubadour poetry. The esthetic study focuses on poetic craft, knowledge of medieval rhetoric, and the usage of stylistic devices.Volume176 in the North Carolina Studies in the Romance Languages and Literatures series.